Biodegradation of paraffin wax by crude Aspergillus enzyme preparations for potential use in removing paraffin deposits. (12th August 2015) - Zhang, Junhui; Xue, Quanhong; Gao, Hui; Wang, Ping
<x xml:space="preserve">Abstract</x> Paraffin deposition problems have plagued the oil industry. Whist mechanical and chemical methods are problematic, microbiological method of paraffin removal is considered an alternative. However, studies have mainly investigated the use of bacteria, with little attention to the potential of fungi. The performance of six Aspergillus isolates to degrade paraffin wax was evaluated under laboratory conditions using solid enzyme preparations. The results showed that all the six enzyme preparations efficiently improved the solubility of paraffin wax in n‐hexane and degraded n‐alkanes in paraffin wax. The degradation process was accompanied by dynamic production of gases (CO2 and H2) and organic acids (oxalate and propionate). The shape of wax crystals markedly changed after enzymatic degradation, with a rough surface and a loose structure. This study indicates that extracellular enzymes from Aspergillus spp. can efficiently degrade paraffin wax. These enzyme preparations have the potential for use in oil wells with paraffin deposition problems.